Linking Sustainability to Loyalty: The Mediating Role of Brand Image in Local Restaurant Branding - Rivena Yasin; Deske W. Mandagi (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to examine the effect of sustainable branding on customer loyalty, with brand image as a mediating variable in the context of local restaurants. Research Method: This research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the proposed relationships. Data were collected through an online survey from 138 customers of local restaurants in North Sulawesi, Indonesia. Results and Discussion: The findings reveal that brand image has a significant positive effect on customer loyalty. The People and Planet dimensions of sustainable branding significantly influence brand image but do not directly affect customer loyalty; instead, their effects are fully mediated by brand image. In contrast, the Prosperity dimension does not significantly influence brand image but demonstrates a strong direct effect on customer loyalty. These results indicate that sustainable branding operates through dual pathways: an indirect, perception-based mechanism via brand image (People and Planet) and a direct, value-based mechanism (Prosperity). Implications: This study contributes to the literature by providing a contextual application of sustainability-driven branding in the restaurant industry and offers practical guidance for managers on how to strategically leverage sustainability initiatives to strengthen brand image and foster long-term customer loyalty.